Extinction of endemic taxa as a direct consequence of global climate change - Monroy-Gamboa, Alina Gabriela; Cab-Sulub, Leticia; Alvarez-Castañeda, Sergio Ticul (THERYA, 2022)
Global climate change occurs from both natural and anthropic causes. Anthropic climate change has effects at various scales and occurs faster than the adaptation of species to these changes. Protected natural areas have been created to preserve species from the different threats facing them. Sierra La Laguna is a sky island with almost no anthropic pressure given its natural isolation; it is home to several endemic taxa, including Peromyscus truei lagunae and Sorex ornatus lagunae. This study aims to assess the possible impact of climate change on species endemic to a sky island exposed to virtually no local anthropic pressure. The Sierra La Laguna sky island, located in the southern region of the Baja California peninsula, harbors different vegetation types, including an oak-pine forest at the highest elevations and xeric vegetation at lower ones. Ecological niche models were developed under three climate change scenarios contemplating temperature rises of 1.5 °C and 4.4 °C. There are insufficient localities to make statistically robust models for mammalian species. Therefore, we used plant species typical of the oak-pine forest (Pinus cembroides lagunae, Quercus brandegeei, and Q. devia) and the rodents Peromyscus eva, that thrives in dry deciduous forests, and Chaetodipus rudinoris and C. spinatus, associated with xeric ecosystems. The models show that ecological suitability for the oak species decreases, while it is completely lost for the pine species. On the other hand, P. eva broadens its elevational range, while C. rudinoris and C. spinatus increase their ecological suitability in both area and elevation. The Sierra La Laguna sky island is an area with virtually no regional or local anthropic pressure. Nonetheless, the projections conducted under various climate change scenarios show a loss of up to 100 % of the area of climatic and elevational suitability for species characteristic of the oak-pine forest even with the minimum temperature rise of 1.5 °C. These results suggest that, under these conditions, endemic species such as P. t. lagunae and S. o. lagunae will become extinguished despite the absence of local anthropic pressures.